Charging Up the Periphery: Glial Ionic Regulation in Sensory Perception - Ray, Sneha; Singhvi, Aakanksha (Frontiers in Cell and Developmental Biology, 2021)
The peripheral nervous system (PNS) receives diverse sensory stimuli from the environment and transmits this information to the central nervous system (CNS) for subsequent processing. Thus, proper functions of cells in peripheral sense organs are a critical gate-keeper to generating appropriate animal sensory behaviors, and indeed their dysfunction tracks sensory deficits, sensorineural disorders, and aging. Like the CNS, the PNS comprises two major cell types, neurons (or sensory cells) and glia (or glia-like supporting neuroepithelial cells). One classic function of PNS glia is to modulate the ionic concentration around associated sensory cells. Here, we review current knowledge of how non-myelinating support cell glia of the PNS regulate the ionic milieu around sensory cell endings across species and systems. Molecular studies reviewed here suggest that, rather than being a passive homeostatic response, glial ionic regulation may in fact actively modulate sensory perception, implying that PNS glia may be active contributors to sensorineural information processing. This is reminiscent of emerging studies suggesting analogous roles for CNS glia in modulating neural circuit processing. We therefore suggest that deeper molecular mechanistic investigations into critical PNS glial functions like ionic regulation are essential to comprehensively understand sensorineural health, disease, and aging.